Partial Characterization of Novel Bacteriocin SF1 Produced by Shigella flexneri and Their Lethal Activity on Members of Gut Microbiota - Carlos Padilla; Verónica Carrasco-Sánchez; Andrés Padilla; Olga Lobos (International Journal of Microbiology)
A strain of Shigella flexneri producing bacteriocin was isolated from a patient with diarrhea. The main objective of this study was to isolate and partially characterize the bacteriocin. The producing microorganism was identified using biochemical, serological, and molecular methods. The lethal activity of the S. flexneri strain was studied using the drop method. This bacterial strain showed activity against different strains of E. coli and B. fragilis. Using immunological techniques, it was determined that S. flexneri belongs to serotype 2a, and by PCR, the presence of the ipaH plasmid was determined. By chromatographic techniques, it was determined that the bacteriocin is a peptide of high purity with a molecular weight of 66294.094 Da. The amino acid composition and sequence were determined by the Edman reaction, and a sequence of 619 amino acid residues was obtained. Only in five positions of this sequence, the amino acid glutamine changed to glutamic acid with respect to colicin U produced by S. boydii. From an ecological point of view, it could be assumed that SF1 bacteriocin contributes to eliminate some members of the normal microbiota of the human intestine, facilitating colonization and then producing the invasion process that characterizes the pathogenicity of Shigella.